The Medicalization of Workplace Sexual Violence on Canadian University Campuses in the #MeToo Era - Petit-Thorne, Alexandria (Anthropologica, 2020)
<span style="color: #000000; font-family: 'Open Sans', Arial, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The #MeToo movement has met institutional barriers to addressing workplace sexual violence in practice. Structural barriers to reporting workplace sexual harassment at Canadian universities are maintained through sexual violence policies that reduce sexual violence to physical assault. Institutional focus on physical forms of sexual violence can be considered the product of medicalization, which allows sexual violence to be conceptualised solely around assault of the body proper. This has limited the legal, criminal and medical responses available to survivors by minimising forms of sexual violence that do not involve physical contact – like sexual harassment and stalking – but have significant impacts on survivors’ lives. In this vein, workplace sexual violence policies put focus on physical assault and limit the scope of the continuum of sexual violence in practice, solidifying barriers to the reporting, investigation and redress of workplace harassment. This article examines the effects of sexual violence medicalization in practice through an ethnographic exploration of reporting workplace harassment.